MENINGKATKAN AKTIVITAS FISIK ANAK-ANAK AUTIS MELALUI PEMBELAJARAN OLAHRAGA DI TAMAN KANAK-KANAK - Mardianah, Rini Ros; Vindyastuti, Ade; Aprianti, Ema (IKIP Siliwangi, 2018)
The research is based on the physical diversity of early childhood who have different background. The purpose of this research is to know the condition of physical activity development of autistic children in kindergarten through sports learning, to know the procedure and process of exercise learning to increase physical activity of autistic children in kindergarten, and to know the results of implementation of the implementation of sports learning for children with autism in kindergarten. The formulation of the problem in this research is how the application of sports learning in increasing the physical activity of autistic children. The research method used is classroom action research method. The results showed that with the learning of sports can increase the physical activity of autistic children in kindergarten by 63% and children of autism kindergarten more able to explore his gestures well. The recommendation of this research is the need for the provision of facilities and infrastructure to support the physical activity of autistic children, the need to develop the ability of the exploration of physical movement, and the need to apply sports learning in children with autism in kindergarten.